The Semantic Analysis of the Security in the Holy Quran Based on the Theory of the Orientational Metaphors - Muhammad Hossein Shirzad; Muhammad Hasan Shirzad; Muhammad Sharifi (آموزه‌های قرآنی, 2021)
The “security” is one of the most essential needs of the human communities which it has been comprehensively paid attention by the holy Quran. Although some of the Quran scholars try to debate over the security teachings of this Book but studying their works shows that most of them examine the Quran verses which directly indicate the management of the earthly human fears and concerns such as the verse 60 of the Anfal surah whereas the great part of the Quranic teachings about security has been shaped not in the form of applying words in their real meaning but in the form of applying metaphor for the innovative conceptualizations. To study this metaphoric language this present paper tries to utilize the cognitive semantics and it is debated the role of the six orientations in creating the conceptual metaphors from security and insecurity. This research shows that security is expressed the linguistic representation in the form of the orientations “up, front and right” in the Quran language while insecurity is conceptualized in the form of the orientations “down, back and left”.